The Effect of Production Costs and Sales Volumes on Profits of Registered Food and Beverage Sub-Sector Manufacturing Companies on the Indonesia Stock Exchange for the 2018-2022 Period - Bambang Purwoko; Moc Aminudin Hadi; Ahmad Gamal; Wiwik Prihartanti (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of production costs and sales volume on the profits of sub-food and beverage manufacturing companies for the period 2018-2020. The type of data used in this study is secondary data. The sampling technique used purposive sampling. The population in this study amounted to 26 companies and the samples taken were 9 companies. The analysis used was the Normality Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, t test, F test, and the coefficient of determination. The results showed that production costs and sales volume partially and significantly influenced the profits of the food and beverage sub manufacturing companies, because the value of tcount > ttable. Simultaneously production costs and sales volume affect the profits of sub-food and beverage manufacturing companies, because the value of Fcount > Ftable. The most dominant variable affecting the profit of the food and beverage sub manufacturing company is the production cost variable of 4.079 with a significant level of 0.000. The value of the coefficient of determination shows 62.4%, while the remaining 37.6% is influenced by other variables not examined in this study.